Household perceptions, practices, and experiences with real-world alternating dual-pit latrines treated with storage and lime in rural Cambodia - James Harper; Rana Abdel Sattar; Tyler Kozole; Veasna Toeur; Jennifer Rogla; Marlaina Ross; Nate Ives; Hannah Pruitt; Payal Soneja; Drew Capone (PLoS ONE, 2025)
Achieving universal safely managed sanitation (SMS) is an ambitious long-term goal in resource-limited rural areas. The non-governmental organization, iDE, introduced the alternating dual-pit latrine (ADP), which treats fecal sludge (FS) on-site using storage and lime to increase SMS in rural Cambodia. However, SMS via ADPs requires adherence to recommended practices (e.g., how and when to switch between pits). We surveyed 765 rural households with ADPs across five of 25 Cambodian provinces to understand how real-world household sanitation practices and knowledge affect and are related to adherence to recommended practices at scale. We calculated summary statistics of household survey responses and used regression models of composite indices to describe how households’ practices and attitudes related to ADPs affect adherence to recommended ADP practices. By 24 months after training, three in five households did not recall how long treatment must proceed until emptying can be performed safely. No household waited the recommended two years to empty their pits. While households appreciated the advantages of owning an ADP (e.g., reduced costs and required land area compared to single-pit latrines over time), no household followed recommended treatment practices. This lack of adherence could have health and environmental implications for households using ADPs. Household practices also varied by province, flood proneness, and education level, adding complexity to how to improve adherence; for example, having at least one household member that completed formal education surprisingly reduced compliance with recommended ADP practices. Household behaviors impact the use and maintenance of on-site sanitation systems in rural areas, with proper adherence is necessary to achieve sustained SMS. Increased access to affordable and safe emptying service providers could enable households to manage the pits of their ADPs and dispose of FS in-situ according to treatment duration, while also ensuring that household practices in operating on-site sanitation systems are integrated into the design, installation, and SMS monitoring of such systems.